Depression among Armed Police Force Serving in Battalion of Kaski - Regmi, Suruchi; Shrestha, Saphalta (Journal of Nursing and Health Sciences Nepal, 2025)
Background: Depression is growing mental health concern globally, and personnel in services like armed police force are particularly vulnerable due to exposure to high-stress environments, irregular work hours, exposure to traumatic events. The aim of the study was to assess the depression among armed police force serving in battalion of Kaski. Methods: A descriptive cross sectional research design and probability simple random sampling technique was used for the study and calculated sample size was 159. Structured self-administered questionnaire was used to collect the data. Informed written consent was taken from each respondent prior to data collection. The collected data were analyzed using SPSS version 22. Descriptive statistics (i.e., frequency, percentage, mean and standard deviation) were used to describe the findings. Inferential statistics (i.e., chi square test) was used to measure the association of the level of depression with selected variables. Results: out of 159 respondents, 15(9.4%) showed signs of mild mood disturbances, 3(1.9%) had borderline clinical depression, 1(0.6%) had moderate depression, and 1(0.6%) had severe depression). Depression levels were found significantly associated with alcohol drinking (p=0.025). Conclusion: The study concludes that few of the armed police force having prevalence of depression and there was statistical significant association between depression and alcohol drinking habits, highlighting the need for regular screening and mental health interventions along with awareness programs focused on prevention of alcohol consumption.